Factors Leading to Public-Private Partnerships and Their Effect on Infrastructure Development: An Empirical Study from Developing Countries - Wickramarathne, I.K.W.N. (Colombo Economic Journal, 2024)
This paper examines the determinants of Public-Private Partnerships (PPPs) in infrastructure development, focusing on the role of income levels in shaping their distribution across 128 developing countries. While PPPs have become increasingly prevalent in developing economies, existing literature has inadequately addressed the role of income levels, which influence the feasibility, attractiveness, and sustainability of PPPs in emerging markets. This study employs Poisson, Negative Binomial, and Tobit regression models, leveraging the World Bank's Private Participation in Infrastructure (PPI) panel dataset from 2000 to 2022. The results reveal that regulatory quality and prior experience with PPPs significantly determine the number and value of PPP investments in developing countries. The effect of regulatory quality and fiscal deficit on the PPP investment in Low-Income countries (LICs) is more significant than that of Lower-middle-income countries (LMICs) and Upper-middle-income countries (UMICs). This paper concludes that the impact of each determinant varies depending on a country's income status, underscoring the need for policymakers in developing countries to tailor their strategies accordingly.
Keywords: Public-private partnerships; Infrastructure; Developing countries; Income level; Count data; Censored data